A novel hydromechanical hybrid motion system for construction machines. Issue 1 (2nd January 2017) - Pettersson, Karl; Heybroek, Kim; Mattsson, Per; Krus, Petter
Abstract: This paper deals with a novel type of hybrid motion system for construction machines based on a common pressure rail shared between a hydromechanical power-split transmission and secondary controlled work hydraulics. A construction machine with driveline and work functions is a complex coupled motion system and the design of an effective hybrid system needs to take both subsystems into account. Studies on energy efficient hybrid systems for construction machines have hitherto principally focused on one subsystem at a time – work hydraulics or driveline. The paper demonstrates a use case with a specific transmission concept proposal for a medium-sized wheel loader. The system is modelled and simulated using an optimal energy management strategy based on dynamic programming. The results show the benefits of a throttle-free bidirectional link between the machine's subsystems and the energy storage, while taking advantage of the complex power flows of the power-split transmission.